The development and study of self-assembling branched amphiphilic peptide bilayer coated iron oxide and gold nanoparticles - Natarajan, Pavithra (Kansas State University, 2020)
The self-assembling branched amphiphilic peptides interdigitate to form water-filled bilayer delimited vesicles called BAPCs. The peptide bilayer is highly stable due to the inter and intramolecular hydrogen bonding, and the hydrophobic interactions, between peptides of the same and opposite leaflets. We substituted the water-filled core of BAPCs with electron dense iron oxide (BAPc-MNBs) and gold nanoparticles (BAP-AuNPs) by coupling the peptides to their surface. The controlled assembly of the peptides on the nanoparticles, verified by Förster resonance energy transfer assay, further provided experimental evidence that the peptides assemble as a bilayer membrane. The peptide bilayer coated metallic nanoparticles were developed to serve as tools to investigate the surface properties of the branched amphiphilic peptides and as entities that find application in bioanalysis, bioimaging and delivery. Therefore, the newly developed nanoparticles expand the applications of branched amphiphilic peptides beyond their current use as delivery systems. The magnetic property of BAPc-MNBs facilitate sorting and isolation of cells that internalize them and the molecules that bind to their surface. Colorimetric quantification assay used to determine the cellular uptake of BAPc-MNBs revealed that epithelial cells utilized multiple endocytic routes to internalize the nanoparticles. However, the water-filled BAPCs were endocytosed mainly via clathrin mediated and macropinocytic pathways. Hence, we could identify the similarities and differences between the cellular interactions of BAPCs with different core compositions and obtain a fundamental understanding of their cellular uptake routes. In vivo studies further demonstrated that BAPc-MNBs are good quantitative tools. They were widely distributed to different organs in C57BL/6 mice and showed difference in biodistribution between melanoma tumor bearing mice and mice without tumors. BAPc-MNBs are also being explored as probes to quantify the binding of nucleic acids to the peptide bilayer. Thus, the newly developed peptide bilayer coated metallic nanoparticles show great potential as probes to study the surface binding properties of BAPCs and as entities that can be used for various applications.
Keywords: Peptides; Gold; Iron; Nanoparticles; Delivery